Excited-state relaxation dynamics of Re(I) tricarbonyl complexes with macrocyclic phenanthroline ligands studied by time-resolved IR spectroscopy - Blanco-Rodríguez, Ana María; Towrie, Michael; Collin, Jean-Paul; Zális, Stanislav; Vlcek, Antonín (Dalton transactions : an international journal of inorganic chemistry, 2009)
Two sets of supramolecular rhenium carbonyl-phenanthroline complexes were prepared: fac-[Re(Cl)(CO)(3)(N,N)] and fac-[Re(Etpy)(CO)(3)(N,N)](+), where N,N is 2,9-di-anisyl-1,10-phenanthroline (dap) or two related macrocyclic ligands, where the two anisyl groups are connected by a polyether chain of different length and rigidity (m27, m30), which wraps around and above the equatorial Re(CO)(2) group. The excited-state character and relaxation dynamics of these complexes were investigated by picosecond time-resolved IR spectroscopy in the spectral region of C[triple bond, length as m-dash]O stretching vibrations, nu(CO). The results were interpreted with the aid of DFT and TD-DFT calculations of the molecular structures and electron-density redistribution upon excitation. [Re(Cl)(CO)(3)(phen-macrocycle)] in CH(2)Cl(2) have the same type of lowest excited state as analogous acyclic phen or bpy complexes, that is a mixed Re(CO)(3)-->phen and Cl-->phen MLCT/XLCT, together with some pipi*(phen) IL character. Its relaxation dynamics are qualitatively similar to those of phen or bpy complexes. However, relaxation of [Re(Cl)(CO)(3)(m30)] shows a slow kinetics component ( approximately 22 ps) which arises from confined local solvent molecules and/or from conformational movements of the flexible m30 polyether ring. In contrast, attaching anisyl groups at the 2 and 9 phen positions in [Re(Etpy)(CO)(3)(phen-macrocycle)](+) effectively "freezes" excited-state relaxation in MeCN, regardless of the presence of the macrocyclic ring. The lowest excited triplet state has a mixed MLCT/IL character. Restricting the solvent access to the excited chromophore clearly affects both the character and dynamics of the lowest excited state.